Typeface sebagai Elemen Visual Pendukung City Branding di Kota Bukittinggi - Abdah Shalihah; Hendara Afriwan (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
Bukittinggi City is a tourist and cultural hub in West Sumatra Province, boasting a strong identity through physical icons such as the Jam Gadang Clock Tower. However, Bukittinggi's visual identity in public spaces, particularly on signage, is still dominated by generic typefaces that fail to reflect local cultural character. This research aims to design a distinctive typeface for Bukittinggi City, inspired by a stylization of the traditional Minangkabau Saluak Laka motif. This motif was chosen because of its philosophical alignment with the Carano element of Bukittinggi's official emblem and the motto "Saayun Salangkah," which reflects the values ​​of togetherness and unity of the Bukittinggi community. The research method used was a design approach with an exploratory approach through field observations, interviews, literature studies, visual analysis, and the stylization of motif shapes into letter anatomy. The design results in the creation of a display typeface that maintains legibility and readability for application on signage in public spaces. The designed typeface is expected to serve as a visual element supporting Bukittinggi's city branding while consistently strengthening local cultural identity within the city.